Evolution of Air Breathing: Oxygen Homeostasis and the Transitions from Water to Land and Sky. Issue 2 (April 2013) - Hsia, Connie C. W.; Schmitz, Anke; Lambertz, Markus; Perry, Steven F.; Maina, John N.
Abstract: Life originated in anoxia, but many organisms came to depend upon oxygen for survival, independently evolving diverse respiratory systems for acquiring oxygen from the environment. Ambient oxygen tension ( P O2 ) fluctuated through the ages in correlation with biodiversity and body size, enabling organisms to migrate from water to land and air and sometimes in the opposite direction. Habitat expansion compels the use of different gas exchangers, for example, skin, gills, tracheae, lungs, and their intermediate stages, that may coexist within the same species; coexistence may be temporally disjunct (e.g., larval gills vs. adult lungs) or simultaneous (e.g., skin, gills, and lungs in some salamanders). Disparate systems exhibit similar directions of adaptation: toward larger diffusion interfaces, thinner barriers, finer dynamic regulation, and reduced cost of breathing. Efficient respiratory gas exchange, coupled to downstream convective and diffusive resistances, comprise the "oxygen cascade"—step‐down of P O2 that balances supply against toxicity. Here, we review the origin of oxygen homeostasis, a primal selection factor for all respiratory systems, which in turn function as gatekeepers of the cascade. Within an organism's lifespan, the respiratory apparatus adapts in various ways to upregulate oxygen uptake in hypoxia and restrict uptake in hyperoxia. In an evolutionary context, certain species also become adapted to environmental conditions or habitual organismic demands. We, therefore, survey the comparative anatomy and physiology of respiratory systems from invertebrates to vertebrates, water to air breathers, and terrestrial to aerial inhabitants. Through the evolutionary directions and variety of gas exchangers, their shared features and individual compromises may be appreciated. © 2013 American Physiological Society. Compr Physiol 3:849‐915, 2013.